Field responses of Glossina pallidipes and Glossina fuscipes fuscipes tsetse flies to Novel Repellent Blend and Waterbuck Repellent Compounds in Kenya. - Benson M Wachira; Richard Echodu; Johnson O Ouma; Imna I Malele; Daniel Gamba; Michael Okal; Kennedy O Ogolla; Clement Mangwiro; Robert Opiro; Deusdedit J Malulu; Bernard Ochieng; Raymond E Mdachi; et al. (PLoS Neglected Tropical Diseases)
Control of tsetse flies constitutes a cornerstone of trypanosomiasis control and elimination efforts in Africa. The use of eco-friendly odor-based bait technologies has been identified as a safer method for control of tsetse flies. These technologies are significantly augmented by development of effective repellents that reduce contact between trypanosome-infected tsetse flies and their vertebrate hosts. Waterbuck Repellent Compounds (WRC) and Novel Repellent Blend (NRB) are recently developed tsetse fly repellent formulations. Information on relative efficacy of these formulations against major tsetse fly vectors of trypanosomiasis in Kenya is limited. Such information can inform choices of repellent technology for optimal control of the flies. Here we assessed relative field responses of Glossina pallidipes and G. fuscipes fuscipes, representative of savannah (morsitans) and riverine (palpalis) groups of tsetse flies, respectively. We deployed NG2G traps or sticky panels and tiny targets using randomized Latin Square experimental design. We then assessed catches of G. pallidipes or G. f. fuscipes respectively on the traps/panels in the absence or presence of WRC or NRB. We additionally baited the NG2G traps with G. pallidipes-responsive 3-propylphenol, octenol, p-cresol, and acetone (POCA) attractant blend, that effectively served as proxy for the preferred vertebrate natural host. We performed the G. pallidipes and G. f. fuscipes experiments in Shimba Hills National Reserve and Ndere Island National Park respectively in Kenya and incorporated a no-odor control for each set of experiments. Mean catches of male G. pallidipes in traps without odor (control), baited with POCA, POCA with WRC or POCA with NRB were 9.86 (95% CI; 6.50- 14.74), 42.71 (95% CI; 28.11 - 64.62), 14.30 (95% CI; 8.50 - 23.60) and 3.03 (95% CI; 0.89 - 7.59) respectively, while for females, the catches were 24.43 (95% CI; 13.65 - 47.42), 70.93 (95% CI; 42.95 - 120.50), 23.85 (95% CI; 16.33 - 37.84) and 6.82 (95% CI; 3.59 -17.02) flies per trap per day respectively. Consequently, the NRB was 4.72 and 3.50-folds and significantly (P < 0.001) more repellent to male and female G. pallidipes respectively, than WRC. In contrast, catches of G. f. fuscipes on targets were similar (P > 0.05) across all the three treatments (including no-odor control). The NRB and WRC are thus efficacious against G. pallidipes but not G. f. fuscipes, with efficacy of NRB being several-folds that of WRC against G. pallidipes. Whether these profiles represent general responses of morsitans and palpalis group of tsetse flies remains to be determined. Additionally, G. f. fuscipes merits further research to formulate an effective repellent against this fly. The NRB can potentially provide better protection to vertebrate hosts, including humans and their livestock than WRC from G. pallidipes. Consequently, NRB can be integrated into routine trypanosomiasis control program to stem transmission of trypanosomes by G. pallidipes, especially in eastern and southern Africa where G. pallidipes is naturally abundant.